Reniform Nematode, Rotylenchulus reniformis Linford & Oliveira (Nematoda: Tylenchida: Tylenchoidea: Hoplolaimidae: Rotylenchulinae) - Koon-Hui Wang (EDIS)
Reniform nematodes in the genus Rotylenchulus are semiendoparasitic (partially inside roots) species in which the females penetrate the root cortex, establish a permanent-feeding site in the stele region of the root and become sedentary or immobile. The anterior portion (head region) of the body remains embedded in the root whereas the posterior portion (tail region) protrudes from the root surface and swells during maturation. The term 'reniform' refers to the kidney-shaped body of the mature female. There are ten species in the genus Rotylenchulus. Rotylenchulus reniformis is the most economically important species (Robinson 1997 ) and is called the reniform nematode. This document is EENY-210, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2001.